A Theory of Corporate Capital Structure and Investment - Cantillo, Miguel (Review of Financial Studies, 2004)
This article uses a general equilibrium framework to explore the origins and limitations of financial intermediaries. In the model, investors have a generic lending technology that they can improve at a cost. Those who upgrade become intermediaries to exploit their advantage. However, conflicts with depositors will limit the banks' market presence, and they will only lend to moderately endowed firms while bondholders will finance cash-rich corporations. The article also analyzes the extent to which investors adopt the superior lending technique, the nature of bank competition, and how corporate and bank conditions affect interest rates and investment. Copyright 2004, Oxford University Press.